If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + x + 27 + 4x + -33 = 816 Reorder the terms: 27 + -33 + x + x + 4x = 816 Combine like terms: 27 + -33 = -6 -6 + x + x + 4x = 816 Combine like terms: x + x = 2x -6 + 2x + 4x = 816 Combine like terms: 2x + 4x = 6x -6 + 6x = 816 Solving -6 + 6x = 816 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6x = 816 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = 816 + 6 6x = 816 + 6 Combine like terms: 816 + 6 = 822 6x = 822 Divide each side by '6'. x = 137 Simplifying x = 137
| 2/9x10/12x18/25 | | 3.66=5.5x+3 | | 95=y/4-18 | | 3.33=5.5x+3 | | 21x^2+11x-2=0 | | 9x-5=4(3x-2) | | x^5*x= | | 7a+2=2a+4 | | 78/54 | | 400=70t-3t^2 | | 7-27/8 | | -4(-2x-7)6x-7= | | 2(3-m)-3m(m-3)=(6-2m)-3m | | -5x^3= | | 2(5xy-6)+4(8+3x)-6=0 | | 4x/9-8y=5 | | 297=(x+2)3x | | 20+4b-5a-ab= | | 2x+3y=49 | | (11x/4)=(2x/5) | | -6+2(5+8)-3= | | -3x+4x-2+5= | | (8x-3)(x+4)= | | 2x-5/8y=1/6 | | 6p+29-34=919 | | 17f+6-7f=2 | | 0=3x^2-6x-297 | | (z^(5/2)*x^(-4))^(1/3) | | 9t^3-144t=0 | | (9a^3+a-3)-(6-3a^3-8a^2)= | | 8y^9-8y^8-96y^7=0 | | (z^(5/2)*x^-4)^(1/3) |